Benin [In West African agriculture and climate change: A comprehensive analysis] - Lawin, Agnidé Emmanuel; Akponikpè, P. B. Irénikatché; Jalloh, Abdulai; Nelson, Gerald C.; Thomas, Timothy S. (International Food Policy Research Institute, 2013)
Benin covers a land area of 114,763 square kilometers and occupies a long stretch of land perpendicular to the coast of the Gulf of Guinea in West Africa. It is bordered on the north by Burkina Faso and the Republic of Niger, on the east by the Federal Republic of Nigeria, and on the west by the Republic of Togo. With a 124-kilometer coastline, it stretches north to south some 672 kilometers and east to west 324 kilometers at its widest point. Most of the country experiences transitional tropical conditions, with less rainfall than in other areas at the same latitude—a climate known as the Benin variant, marked by a dry season from November to early April and a rainy season from mid-April to October.